2021
DOI: 10.32725/kont.2021.031
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to care and missing services from the point of view of informal caregivers in the South Bohemian Region

Abstract: Introduction: Due to the need and current relevance, informal care as a part of the long-term care system as well as the issue of caregivers are included in the Czech National Strategy for the Development of Social Services between 2016 and 2025. Goal: The goal of this qualitative research was to identify selected areas that informal caregivers encounter in connection with the care of a loved one in the home environment in the South Bohemian Region. The partial goal was to find out what problems informal careg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…Conflicts can easily arise due to the contradictory nature of these roles and the demands placed on the caregivers; on the one hand, the effort to "Do everything for him / her", on the other hand frustration at the hopeless situation of the approaching the death of a loved one and their own physical and psychological limits and ignorance. Our research confirmed the conclusions of Hajduchová et al (2021) and Brémault-Phillips et al (2016) that on the part of family caregivers, there is insufficient knowledge in the area of nursing competencies and a lack of information about possible available services, which, as a result, increases the physical and mental burden. This burden is a very common and well-studied phenomenon of caring for a dying person at home.…”
Section: Discussionsupporting
confidence: 88%
“…Conflicts can easily arise due to the contradictory nature of these roles and the demands placed on the caregivers; on the one hand, the effort to "Do everything for him / her", on the other hand frustration at the hopeless situation of the approaching the death of a loved one and their own physical and psychological limits and ignorance. Our research confirmed the conclusions of Hajduchová et al (2021) and Brémault-Phillips et al (2016) that on the part of family caregivers, there is insufficient knowledge in the area of nursing competencies and a lack of information about possible available services, which, as a result, increases the physical and mental burden. This burden is a very common and well-studied phenomenon of caring for a dying person at home.…”
Section: Discussionsupporting
confidence: 88%